PERTUMBUHAN LARVA IKAN KELABAU (Osteochilus melanopleuora) YANG DIBERI PAKAN CACING SUTRA (Tubifex sp.) - Mukhlisah; Rina Iskandar; Ahmad Zakaria (Chlorophyl, 2025)
The nutritional benefits of silkworms have been identified, but the daily percentage of silkworms that provides optimal growth and survival for kelabau larvae has not been thoroughly studied. This study aimed to analyze the effect of different percentages of silkworms on the growth of kelabau larvae. This experimental study was conducted using a Completely Randomized Design at the Mandiangin Freshwater Aquaculture Center, Karang Intan District, South Kalimantan, for 10 days. Three treatments with three replications were fed silkworms at 10%, 20%, and 30% of the total weight of the test fish per day. The 30% feeding rate in treatment C resulted in optimal growth of kelabau larvae, followed by treatment B, while treatment A produced the lowest growth in absolute weight, mean absolute length, and SGR. The highest survival rate (SR) was obtained in treatment C at 95%, followed by treatments A and B at 87%.